Synovial Lesions in Experimental Canine Lyme Borreliosis - Susta, L.; Uhl, E. W.; Grosenbaugh, D. A.; Krimer, P. M. (Veterinary pathology, 2012)
Borrelia burgdorferi is the causative agent of Lyme disease, which is mainly characterized by lameness in dogs. More than 95% of naturally infected dogs are asymptomatic or subclinical; however, in experimental studies, histologic synovial lesions are consistently observed in asymptomatic dogs inoculated with B. burdgorferi. This study investigates the ability of a synovial histopathologic scoring system, clinicopathologic data, and polymerase chain reaction (PCR) testing to differentiate between B. burgdorferi–infected and uninfected dogs. Eighteen 18-week-old beagles were subject to challenge with B. burgdorferi–infected wild-caught ticks (Ixodes scapularis), and 4 uninfected dogs served as controls. Infection was confirmed by serology (ELISA) and PCR amplification of B. burgdorferi–specific DNA of skin biopsies taken at the tick attachment site. A synovial scoring system from human medicine was adapted and implemented on postmortem synovial samples to discriminate infected and noninfected animals. Application of this system to elbows and stifles with a cumulative joint score cutoff  > 4 showed a sensitivity of 88.2% and a specificity of 100%, with a positive likelihood ratio of infinity and a negative likelihood ratio of 0.12. Complete blood count, serum biochemistry, urinalysis, urine protein:creatinine, urine PCR, synovial and lymph node cytology, and synovial PCR were evaluated but were not reliable indicators of clinical disease.